Inhibition of HMGB1 Suppresses Hepatocellular Carcinoma Progression via HIPK2-Mediated Autophagic Degradation of ZEB1 - Zhu, Wei; Li, Jun; Zhang, Yuheng; Zhu, Zhengyi; Liu, Hanyi; Lin, Yunzhen; Hu, Anyin; Zhou, Jingchao; Ren, Haozhen; Shi, Xiaolei (Frontiers in Oncology, 2021)
Autophagy is a conserved catabolic process maintaining cellular homeostasis and reportedly plays a critical role in tumor progression. Accumulating data show that autophagic activity is inhibited in hepatocellular carcinoma. However, the underlying molecular basis of impaired autophagy in HCC remains unclear. In this study, we revealed that autophagic activity was suppressed by HMGB1 in a HIPK2-dependent way. Targeting HMGB1 could inhibit the degradation of HIPK2, as a result of which, autophagic degradation of ZEB1 was enhanced by reprogramming glucose metabolism/AMPK/mTOR axis. Moreover, we demonstrated that selectively degradation of ZEB1 was responsible for HCC growth inhibition in HMGB1 deficient cells. Lastly, we found the combination therapy of HMGB1 inhibitor and rapamycin achieved a better anti-HCC effect. These results demonstrate that impaired autophagy is controlled by HMGB1 and targeting HMGB1 could suppress HCC progression via HIPK2-mediated autophagic degradation of ZEB1.